Ethic in student's life : communication ethics / Fahada Nur Mohamad Izhar... [et al.] - Mohamad Izhar, Fahada Nur; Omar, Muhammad Akid; Mohd Ridzuan, Nur Ain Danishah; Jumaat, Muhamad Adham; Azhar, Fadha Nur (2019)
Communication is an inseparable feature of human life. According to a book (Communication Skills and Soft Skills: An Integrated Approach, 2011). It includes all the activities of a person from his birth to death. We cannot think of passing even a single day without any short of communication. The scope or uses of communication cannot be demarcated, its importance is indispensable for all. There are rules in communication that we need to adapt in our daily life to have a better and good communication. For instant, as a humble of human being, we need to have the ethics when we are having a conversation with everyone. It is really important because the good ethics will lead to a harmony and create good surrounding around them.